The Influence of Satisfaction, Trust and Price on Garuda Indonesia Passenger Loyalty at Sultan Hasanuddin Makassar International Airport - Rachmawati , Avianita; Rolaskhi, Shadli; Maya Hapsari, Ira (Journal of Management, 2024)
This study investigates the impact of inclusive marketing strategies on consumer perceptions, with an emphasis on the moderating role of consumer experience with inclusive campaigns. This study used a quantitative approach, collecting data from 100 respondents through a structured questionnaire. Data were analyzed using structural equation modeling (SEM) to test the direct and moderating relationships between variables. The results showed that inclusive marketing has a significant and positive influence on consumer perception, with a coefficient of 0.708 and a P-value of 0.000. In addition, consumer experience also shows a significant direct effect on consumer perception (coefficient = 0.315, P-value = 0.000). However, the moderating effect of consumer experience in the relationship between inclusive marketing and consumer perception was not statistically significant (coefficient = 0.049, P-value = 0.146). These findings suggest that inclusive marketing alone can significantly shape positive consumer perceptions, regardless of consumers' prior experience with the campaign